A study on new market development using a hybrid of QFD and ANP - Seyedeh Rashedeh Makhzan Mousavi; Zahra Alipour Darvishi (Management Science Letters)
This paper presents an empirical investigation on new product development (NPD) using a hybrid of quality function deployment (QFD) and analytical network process (ANP). The study is accomplished in one of the biggest auto producers in Iran named Saipa. The study examines whether or not NDP influences positively on critical success factors (CSF) and knowledge management (KM). The study also examines whether KM influences on success of NPD. Using some statistical tests, the study confirms that NDP influences on CSF and KM and there is a positive and meaningful relationship between KM and success of NPD. In addition, the study has prioritized various factors for development of new product development and determined that “technology application consistent with customer’s needs” as well as “Having various meetings with different departments” are the most important factors for the success of new product development.